1988
DOI: 10.1002/cyto.990090102
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage, cytotoxic effect and cell‐cycle perturbation of Hoechst 33342 on L1210 cells in vitro

Abstract: This study was designed to evaluate the effects of vital dye Hoechst 33342 (HO 33342), at concentrations used to obtain a good DNA histogram resolution, on DNA integrity, cell growth, and cell-cycle phase distribution of Ll210 cells. HO 33342 exposure for 2 h, at 37°C produced DNA single-strand breaks as assessed by the method of alkaline elution. DNA single-strand breaks were concentration dependent (in the range .5-5 pg/ml) and increased significantly when HO 33342 (0.5-1.5 pg/ml) was associated with exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 19 publications
0
26
1
Order By: Relevance
“…After 51Cr, H33342 was the least attractive of the labelling methods evaluated. Even low doses of H33342 have been reported to interfere with cell proliferation [6] and in our hands, spontaneous loss of H33342 from the A-LAK cells led to an underestimation of the cell recovery (Table 4). Furthermore, the extensive uptake by liver phagocytes of H33342 released from dead cells, as previously described [2], impedes the distinction between viable and dead A-LAK cells.…”
Section: Diseussioncontrasting
confidence: 51%
“…After 51Cr, H33342 was the least attractive of the labelling methods evaluated. Even low doses of H33342 have been reported to interfere with cell proliferation [6] and in our hands, spontaneous loss of H33342 from the A-LAK cells led to an underestimation of the cell recovery (Table 4). Furthermore, the extensive uptake by liver phagocytes of H33342 released from dead cells, as previously described [2], impedes the distinction between viable and dead A-LAK cells.…”
Section: Diseussioncontrasting
confidence: 51%
“…However, it also was demonstrated previously that Hoechst 33342 dye has cytotoxic effects on cultured lymphocytes (35). This raises the possibility that Hoechst high /non-LRTC failed to form tubular structures or integrate into the developing nephron because of Hoechst toxicity.…”
Section: Discussionmentioning
confidence: 87%
“…3) is very similar to that obtained by mitotic shaking (241, drug blockage (19,25), centrifugal elutriation (14,21), or DNA content analysis and sorting (13). One advantage of volume sorting over use of DNA content analysis with vital dyes is the lack of the cytotoxicity, mutagenicity, and cell cycle perturbation induced by DNA staining and laser illumination (2,4,21). The data in this article and in previous ones by our group (5,7) have demonstrated that there is essentially no toxicity associated with volume cell sorting.…”
Section: Discussionmentioning
confidence: 99%